Case Study: The Use of Recast in the EYL Classroom - Dede Shandra; Gunawan Suryoputro (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2017)
This paper reports the use of recast technique in correcting students’ errors in the EYL (English for Young Learners) classroom. Observation and interview methods were conducted to collect the data. While observation was implemented to find out the role of recast in teaching-learning processes, interview to ten teachers and twenty-four students was conducted in order to answer teachers and students’ perceptions of recast technique. Findings showed that teachers and students gave positive perceptions of recast. Recast can encourage students’ language awareness, motivation, and independence. The findings of this study suggest that recast technique can be used as an alternative feedback in giving correction to students’ errors. The study confirms literature showing that recast is an effective corrective feedback.